Smart textiles "smart textiles" : proceedings of the focused session A-11 "smart textiles" of symposium A "Smart materials and micro/nanosystems", held in Acireale, Sicily, Italy, June 8-13 2008 as part of CIMTEC 2008-3rd International conference "Smart materials, structures and systems" - Vincenzini, P., 1939-; Paradiso, Rita (Trans Tech Publications Ltd, 2008)
"This book contains selected, peer reviewed papers from the Focused Session A-11 "Smart Textiles" of Symposium A "Smart Materials and Micro/Nanosystems", held in Acireale, Sicily, Italy, June 8-13, 2008 as part of CIMTEC 2008 - 3rd International Conference "Smart Materials, Structures and Systems". This timely collection comprises of 24 peer-reviewed papers which, between them, present a comprehensive survey of smart textiles. The papers are grouped into topics including adaptive/active textiles; E-textiles; and functionality and applications."--Knovel.
Vol. 7 of 8 volumes from the 3rd International Conference "Smart Materials, Structures and Systems."
Keywords: Smart materials -- Congresses.; Smart structures -- Congresses.; elektronické knihy; electronic books